Energy price shocks and stabilization policies in a multi-agent macroeconomic model for the Euro Area - Enrico Turco; Davide Bazzana; Massimiliano Rizzati; Emanuele Ciola; Sergio Vergalli (Fondazione Eni Enrico Mattei (FEEM), 2022)
Soaring energy prices since fall 2021 have prompted European governments to introduce policy measures to support households and businesses. In this paper, we employ the MATRIX model, a multi-sector and multi-agent macroeconomic model calibrated on the Euro Area, to analyze the economic and distributional effects of different types of macro-stabilization policies in response to energy price shocks. Simulation results show that, in the absence of stabilization policies, an increase in fossil fuel price would lead to a sharp growth in price inflation and a severe contraction in real GDP, followed by a slow but steady recovery. We find no significant effects of generalized tax cuts and household subsidies, while firm subsidies promote a faster recovery but at the expense of greater financial instability in the medium term due to the resulting market distortions. If timely adopted, government-funded energy tariff reduction is the most effective policy in mitigating GDP losses at relatively low public costs, especially if coupled with an extra-profit tax on energy firms. Energy entrepreneurs benefit from rising fuel prices in all policy scenarios, but to a lesser extent under energy tariff cuts and windfall profits tax, favouring, in that case, workers and downstream firms owners.
Keywords: C63; E63; O13; Q43; 330; Energy shocks; Policy analysis; Agent-based models; Macroeconomic dynamics